2000
DOI: 10.1097/00005053-200012000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Spontaneous Improvement Rates in Depressed Outpatients

Abstract: The objectives of the present report were: a) to determine the spontaneous remission rate in depressed outpatients who do not receive antidepressant medication; b) to develop a novel method for obtaining a control group that can be used to gauge the effectiveness of antidepressant medication in clinical practice; and c) to compare response rates from the present sample with outcomes of depressed patients in our practice who were treated with antidepressant medications. By using a naturalistic design, prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…In fact, at end point, almost one-third of the original sample was receiving treatment with an augmentation strategy. The response and remission rates observed in our study are in accordance with response rates from a number of other naturalistic studies of MDD [15][16][17][18][19] and support the notion that improvement with residual symptoms is the most common outcome among MDD patients treated in outpatient settings. Cuffel et al, 19 for instance, reported a 27% to 39% remission rate among 1859 MDD outpatients during a 3-year period in the national provider network of a managed behavioral health organization.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In fact, at end point, almost one-third of the original sample was receiving treatment with an augmentation strategy. The response and remission rates observed in our study are in accordance with response rates from a number of other naturalistic studies of MDD [15][16][17][18][19] and support the notion that improvement with residual symptoms is the most common outcome among MDD patients treated in outpatient settings. Cuffel et al, 19 for instance, reported a 27% to 39% remission rate among 1859 MDD outpatients during a 3-year period in the national provider network of a managed behavioral health organization.…”
Section: Discussionsupporting
confidence: 90%
“…17,[21][22][23][24][25][26] Without such measures, we are unable to determine where change in symptoms occurred (eg, sleep, mood, etc.). Similarly, no formal measures of medication adherence were used.…”
Section: Discussionmentioning
confidence: 99%
“…Although commonly used as the primary outcome measure in other naturalistic studies and chart reviews (9,(10)(11)(12)(13)(14), and recently reported as a sensitive measure of early global improvement in clinical trials (15), the CGI certainly does not assess specific symptom change as do measures used in other clinical trials (e.g., Hamilton Depression Rating Scale; 16). Without the consistent use among clinicians of more sensitive measures, we are unable to determine where change in symptoms occurred (e.g., sleep, mood, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes of subjects who enrolled in a treatment trial and were randomized to a waiting list provide perhaps the most valid insight we have into the naturalistic course of depression, and a meta-analysis of such studies was conducted by one of the authors (Posternak and Miller, 2001). Another study we conducted (Posternak and Zimmerman, 2001) evaluated outcomes of a cohort of depressed patients who presented for treatment but who ended up not receiving antidepressant therapy for a variety of reasons (e.g., never filled prescription, intolerable side effects). Both studies were limited by modest sample sizes (N ϭ 76 and N ϭ 25, respectively) and their results are, of course, generalizable only to treatment-seeking subjects.…”
mentioning
confidence: 99%